Arms trafficking and "privatization of force". What scenarios? (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The problem of arms trafficking is now part of a framework of wide transformations that affect the traditional distinction between the public and the private spheres, affecting the contemporary articulations of State sovereignty and the use of force in the management of internal security and in the international relations. In this essay, the privatization of force and of the “private” trade of arms (being the latter lawful or illicit) are analyzed in their respective problems, with a particular attention to its relation to the close link with the project that the new neoliberal "rationality" is imposing globally. The recent literature on vulnerability will be therefore investigated, with a double aim: on one hand, it will help to identify a perspective alternative to the one that proposes the dystopian horizon of a society governed by the private use of armed violence. On the other hand, the notion of vulnerability will allow elaborating new and more coherent foundations of a legal and political system oriented towards the protection of fundamental rights and freedoms.Keywords: violence, privatization, neoliberalism, vulnerability, fundamental rights